2018
DOI: 10.1177/0040517518803786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smart textile metamaterials on electromagnetic performance for wireless body area network systems

Abstract: In this work, the utilization of different textile materials for manufacturing of metamaterial with the aim of controlling the signal propagation on smart textile applications is investigated. The performance of composite structures of embroidered yarn conductor transmission lines loaded with split-ring resonator geometries in felt and cotton substrates are reported. The proposed structure allows propagating or filtering the transmitted signal in the microwave frequency range. The experimental results exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, it is observed that the H patterns of radiations have omni-directional radiation properties. According to the radiation results, the radiation patterns show a significant reduction in back lobe radiations as observed from Figures 16,17,18 and 19. Therefore, a considerable enhancement in the proposed design performance is attained.…”
Section: Radiation Patternmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, it is observed that the H patterns of radiations have omni-directional radiation properties. According to the radiation results, the radiation patterns show a significant reduction in back lobe radiations as observed from Figures 16,17,18 and 19. Therefore, a considerable enhancement in the proposed design performance is attained.…”
Section: Radiation Patternmentioning
confidence: 79%
“…WBANs are designed not only for healthcare applications but are also considered for sports and other entertainments. [17][18][19][20] Other developing wireless technologies are also available, such as power transfer, 21 RFID, 22 search and rescue applications 23 and medical applications. 24 However, their main aim is high bandwidth with reduced power consumption.…”
mentioning
confidence: 99%
“…On the other hand, metamaterials (MTMs) [3,4] are an attractive topic for researchers recently, which they have applied for improving microwave systems such as antennas, filters, and sensors [5][6][7]. Recently, MTMs have been integrated into textiles and have led to the development of MTM in a variety of reported fields, such as e-textile metamaterial transmission lines [8], MTM textile sensors [9], MTM microwave absorbers [10], double ring resonators garment antenna [11], and (in the field of filtering) e-textile band pass filters [12]. Furthermore, split-ring resonators (SRRs), which were introduced by [3,13], make an effective magnetic coupling with microstrip topology, that they don't need additional magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials are artificial materials and in desired frequency, they may exhibit extraordinary electromagnetic properties (e.g., negative permeability, negative permittivity, reverse Doppler Effect and negative refractive) [1,2]. Due to these features, it takes place in many applications such as filters [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], antenna [23,24], absorbers [25,26] and sensors [4,5,13,14,16,18,21,22,27,28]. Split ring resonators (SRR) are one of the most preferred structures for electromagnetic metamaterials design [2-5, 8, 14, 18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the applications in which metamaterials are widely used is filters [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In this study, it was aimed to design a band-stop filter for GSM-900 and 2.4 GHz ISM band.…”
Section: Introductionmentioning
confidence: 99%